2011
DOI: 10.1111/j.1755-148x.2011.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma cell invasiveness is regulated by miR‐211 suppression of the BRN2 transcription factor

Abstract: To identify microRNAs potentially involved in melanomagenesis, we compared microRNA expression profiles between melanoma cell lines and cultured melanocytes. The most differentially expressed microRNA between the normal and tumor cell lines was miR-211. We focused on this pigment-cell-enriched miRNA as it is derived from the microphthalmia-associated transcription factor (MITF)-regulated gene, TRPM1 (melastatin). We find that miR-211 expression is greatly decreased in melanoma cells and melanoblasts compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 62 publications
14
171
0
Order By: Relevance
“…5B). Furthermore, it has been shown that MITF regulates TRPM1 gene expression as well as the expression of miR-211-5p, as it resides in the sixth intronic region of TRPM1 (21,22). A significant up-regulation of TRPM1 was confirmed by qPCR (Fig.…”
Section: Braf Inhibition Up-regulates Mir-211-5p Expression Through Mmentioning
confidence: 52%
“…5B). Furthermore, it has been shown that MITF regulates TRPM1 gene expression as well as the expression of miR-211-5p, as it resides in the sixth intronic region of TRPM1 (21,22). A significant up-regulation of TRPM1 was confirmed by qPCR (Fig.…”
Section: Braf Inhibition Up-regulates Mir-211-5p Expression Through Mmentioning
confidence: 52%
“…A combination of BRAF, ␤-catenin, and MITF/miR-211 regulates the amount of BRN2 mRNA and protein (10,24,25,56). In this study, we evaluated the significance of posttranslational modification of conserved residues (Thr361 and Ser362) in the BRN2 DBD for cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This represses BRN-2 [9], the transcriptional repressor of PDE5A [3]. Thus hypoxic melanoma microenvironments generate sub-populations of melanocytes with low MITF and PDE5A levels.…”
Section: Article Bodymentioning
confidence: 99%